2018
DOI: 10.1186/s13068-018-1255-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving enzymatic digestibility of wheat straw pretreated by a cellulase-free xylanase-secreting Pseudomonas boreopolis G22 with simultaneous production of bioflocculants

Abstract: BackgroundXylan removal by bacterial pretreatments has been confirmed to increase the digestibility of biomass. Here, an effective xylan removal technique has been developed to enhance the digestibility of wheat straw and simultaneously produce bioflocculants by a cellulase-free xylanase-secreting strain, Pseudomonas boreopolis G22.ResultsThe results indicated that P. boreopolis G22 is an alkaliphilic strain which can secrete abundant amounts of xylanase. This xylanase had activity levels of 2.67–1.75 U mL−1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…4, S2) that have been previously reported to degrade lignocellulose materials. Pseudomonas boreopolis produces a cellulase-free xylanase with a high activity of hemicellulose degradation [85]. Maki et al [86] reported that Bacillus strain (55S5) and a Pseudomonas strain (AS1) displayed high potential for lignocellulose decomposition due to a variety of cellulase and xylanase activities.…”
Section: Effect Of Eco 2 Concentration On Microbial Community C and N Cyclesmentioning
confidence: 99%
“…4, S2) that have been previously reported to degrade lignocellulose materials. Pseudomonas boreopolis produces a cellulase-free xylanase with a high activity of hemicellulose degradation [85]. Maki et al [86] reported that Bacillus strain (55S5) and a Pseudomonas strain (AS1) displayed high potential for lignocellulose decomposition due to a variety of cellulase and xylanase activities.…”
Section: Effect Of Eco 2 Concentration On Microbial Community C and N Cyclesmentioning
confidence: 99%
“…Soil-derived Pseudomonas species have been recognized as powerful ligninolytic microbes ( 34 , 56 , 57 ). In addition, they can secrete endoxylanases during wheat straw degradation processes ( 58 , 59 ). Moreover, a strong correlation of cellulose degradation with the presence of Paenibacillus species has been reported in a synthetic LMC ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spartina pectinata L., as well as various agricultural residues and other herbaceous plants, could become an important feedstock for the production of biofuels 1 . Lignocellulose biomass is a commonly available and renewable energy source, and 55-75% of it consists of polymers (cellulose, hemicellulose, lignin) by dry weight and can be used for ethanol, as well as for biogas production during the anaerobic digestion (AD) process 2 . However, the main drawback of the lignocellulosic biomass is its structural heterogeneity and complexity causing the native biomass resistance to enzymatic hydrolysis creating thereby an obstacle for the AD process and finally, limiting biogas production.…”
mentioning
confidence: 99%
“…However, the main drawback of the lignocellulosic biomass is its structural heterogeneity and complexity causing the native biomass resistance to enzymatic hydrolysis creating thereby an obstacle for the AD process and finally, limiting biogas production. Hemicelluloses, especially xylan, if coated with crystalline cellulose restricts access to the cellulose microfibrils, making them water insoluble and recalcitrant to biodegradation 2,3 . Moreover, a high content of barely degradable fibre fractions in biomass intended for the production of gaseous biofuels limits the yield of methane produced 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation